Analisis Kebijakan Pengelolaan Sampah Level Rumah Tangga di Kalurahan Baciro, Kota Yogyakarta - Kusuma, Endah Ayu; Hamida, Nindya Christy; Widhianta, Nanda; Setiawan, Qarra Salma; Widinugroho, Yudistira (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
The city of Yogyakarta is one of the contributors to waste at the Piyungan TPST. Waste production in the City of Yogyakarta in 2021 will reach 327 million tons per day with the largest composition of waste being household waste by 55.2%. Baciro Urban Village is one of the sources of waste with a volume of waste generated of 28.57 m3 per day. This study aims to determine the implementation of household waste management in Baciro Village before and after the Zero Inorganic Waste Movement Program policy, factors related to success and obstacles, and the relevance of waste management implementation to health conditions in Baciro Village. The research approach used is a mix method in the form of a combination of qualitative and quantitative approaches. Quantitative analysis was carried out simply by interpreting the data from the questionnaire results in the form of percentage graphs. The results of data processing and analysis show that Baciro Sub-district has implemented the Circular Letter from Pj. Mayor of Yogyakarta Number 660/6123/SE/2022 regarding the Zero Inorganic Waste Movement and succeeded in reducing the final amount of waste disposed of at TPST Piyungan. The existence of the Zero Inorganic Waste Movement Program has brought better development in household waste management in Baciro Kalurahan. The existence of this program has increased community empowerment and the implementation of the waste bank has been able to be monitored to the JSS (Jogja Smart Service) system. However, there are still challenges in terms of regeneration and the contribution of the younger generation. The inhibiting factors of the waste management process are the limited land and waste sorting bins, while the supporting factors for success are if there is sufficient land available and there is an increase in socialization or counseling regarding waste management. The problem of limited land in the implementation of waste banks poses a risk of decreasing public health.